Effects of cooking techniques on fatty acid and oxylipin content of farmed rainbow trout (Oncorhynchus mykiss). Issue 6 (19th August 2017) - Flaskerud, Katrina; Bukowski, Michael; Golovko, Mikhail; Johnson, LuAnn; Brose, Stephen; Ali, Ashrifa; Cleveland, Beth; Picklo, Matthew; Raatz, Susan
Abstract: The aim of this study was to investigate the effect of various cooking techniques on the fatty acid and oxylipin content of farmed rainbow trout. Rainbow trout is an excellent source of long‐chain omega‐3 ( n ‐3) polyunsaturated fatty acids (PUFA) which have beneficial health effects. Fillets of 2‐year‐old farmed rainbow trout were baked, broiled, microwaved, or pan‐fried in corn (CO), canola (CaO), peanut (PO), or high oleic sunflower oil (HOSO). Fatty acids and oxidized lipids were extracted from these samples and their respective raw fillet samples. Fatty acid content was determined using gas chromatography and oxylipin content by mass spectroscopy. The values obtained from each cooking method were compared to those obtained from the respective raw fillets using paired t tests. PUFA content was not altered when samples were baked, broiled, microwaved, or pan‐fried in CO or CaO. Pan‐frying in PO reduced α‐linolenic acid (18:3 n ‐3), eicosadienoic acid (20:2 n ‐6), and dihomo‐γ‐linolenic acid (20:3 n ‐6), while pan‐frying in HOSO reduced 18:3 n ‐3, eicosapentaenoic acid (20:5 n ‐3), docosapentaenoic acid (22:5 n ‐3), docosahexaenoic acid (22:6 n ‐3), linoleic acid (18:2 n ‐6), 18:3 n ‐6, 20:2 n ‐6, 20:3 n ‐6, docosatrienoic acid (22:2 n ‐6), and adrenic acid (22:4 n ‐6) compared to raw fish. Cooking decreased the omega‐6 ( n ‐6) PUFA‐derived oxylipins, but caused no change in 20:5 n ‐3 or 22:6 n ‐3‐derived oxylipins of the fillets. In conclusion, pan‐frying was the only cooking method to alter the fatty acid content of the fillets, while observed changes in oxylipin content varied by cooking method. As the physiological impact of oxylipins is currently unknown, these results suggest that the cooking methods which optimize the consumption of n ‐3 PUFA from rainbow trout are baking, broiling, microwaving, or pan‐frying in CO, CaO, or PO. Abstract : The cooking of farmed rainbow trout affects its fatty acid and oxylipin content depending on the cooking technique used. Pan‐frying in oils results in significant changes.